2019
DOI: 10.1213/ane.0000000000003981
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation Management and Heparin Resistance During Cardiopulmonary Bypass: A Survey of Society of Cardiovascular Anesthesiologists Members

Abstract: We surveyed Society of Cardiovascular Anesthesiologists members regarding anticoagulation practices for cardiopulmonary bypass and attitudes on heparin resistance. Of 550 respondents (18.5% response rate), 74.9% (95% CI, 71.3%–78.5%) used empiric weight-based dosing of heparin, and 70.7% (95% CI, 66.9%–74.5%) targeted an activated clotting time of either 400 or 480 seconds to initiate cardiopulmonary bypass. Of note, 17.1% (95% CI, 13.9%–20.2%) of respondents reported activated clotting time targets lower than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 6 publications
(14 reference statements)
0
28
0
2
Order By: Relevance
“…The advantages of the HMS Plus are as follows: (1) it can be used at the bedside for point-of-care testing, and (2) it can detect inadequate anticoagulation (heparin concentrations below than 3 U/mL during CPB) despite a prolonged ACT. However, the survey of members of the Society of Cardiovascular Anesthesiologists in 2017 demonstrated that only 13.1% of institutions answered that they used heparin concentration to determine adequate anticoagulation for CPB [ 9 ]. This result suggested that heparin concentration measurement devices such as the HMS Plus are not currently available in the majority of institutions providing cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of the HMS Plus are as follows: (1) it can be used at the bedside for point-of-care testing, and (2) it can detect inadequate anticoagulation (heparin concentrations below than 3 U/mL during CPB) despite a prolonged ACT. However, the survey of members of the Society of Cardiovascular Anesthesiologists in 2017 demonstrated that only 13.1% of institutions answered that they used heparin concentration to determine adequate anticoagulation for CPB [ 9 ]. This result suggested that heparin concentration measurement devices such as the HMS Plus are not currently available in the majority of institutions providing cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, women with HR need to take more heparin to prevent thrombosis. 18 HR might be regarded as a state of response to a variable dose of heparin. Therefore, a combination of supplementary LMWH, FFP, or AT concentrate is usually recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, laboratory testing is not universally available and takes 30- There is a lack of consensus on a suitable target ACT for initiation of cardiopulmonary bypass [5]. A 2019 review of international centres showed variation in accepted ACTs [7], with the majority of clinicians targeting an ACT of either 400 s or 480 s to initiate cardiopulmonary bypass [7]. One study suggested that coagulation was activated with an ACT < 300 s and that 480 s should be targeted in order to incorporate a margin of safety [8].…”
Section: Discussionmentioning
confidence: 99%